Yahudi Geleneğinin Dönüşüm Sürecinde Şabat’ın Şekillenmesi/The Shaping of the Sabbath: The Transformative Journey of Jewish Tradition - Merve Yetim; Dursun Ali Aykıt (Oksident)
It is widely acknowledged in academic scholarship that the Jewish religious tradition has undergone significant cultural, legal, and theological transformations across its long and complex history. These shifts are often tied to moments of political disruption, exile, and reinvention, which necessitated new religious articulations and structures of authority. One of the clearest reflections of this historical dynamism is the institution of the Sabbath (Shabbat), whose evolving function and meaning serve as a valuable lens through which broader patterns of change in Judaism can be traced and analyzed. Originally instituted—at least according to tradition—during the Mosaic period as a divinely ordained day of rest marked by the cessation of labor, the Sabbath began as a simple ritual of pause embedded within a covenantal relationship between God and Israel. However, over time, this day of rest evolved into a highly codified legal framework governed by intricate halakhic rulings and interpretive traditions. The Shabbat attributed to Moses can thus be viewed not as a static institution but as the foundational model upon which later, more detailed ritual and legal systems were constructed. Importantly, this transformation did not occur in a single moment or under a unified authority; rather, it unfolded gradually across multiple historical stages and sociocultural contexts. The early textual traces of this evolution are partially preserved in the Hebrew Bible (Tanakh), where Sabbath is presented in various registers—from a creation-oriented cosmological pattern in Genesis to a socially ethical commandment in Deuteronomy. Yet these texts lack the complex legal infrastructure that would later characterize rabbinic Sabbath observance. It was during the Talmudic period that the Sabbath attained its fully developed halakhic form, shaped through the interpretive efforts of rabbinic sages responding to shifting communal needs, theological concerns, and the realities of post-Temple Jewish life. This study explores the historical transformation of the Sabbath by examining its scriptural origins and tracking its gradual legal and theological elaboration through the rabbinic corpus. In doing so, it positions the Sabbath as a paradigmatic case through which to understand how Jewish law, ritual, and identity were renegotiated and redefined in response to the evolving historical conditions of the Jewish people.